UNAS AVES DE CERVANTES, GÓNGORA Y GOYA Y UNOS CANTOS DE MUJERES CONTRA TONTOS IMPOTENTES. - Pedrosa, José Manuel (Andamios)
An analysis of a dramatic scene by Cervantes, a ballad attributed to Góngora or Tirso de Molina, and a work by Goya, which share a common protagonist, a foolish character attempting to ascend to a high place to catch a bird. A comparison is made with other literary works, both oral and written, generally of a carnivalesque nature; and their erotic double meanings are deciphered, since these themes often involve a questioning of the sexual potency of the men, voiced by female characters. There is a reflection on the diversity of literary and artistic genres and formats that convey analogous or related discourses.